Coexpression of Sucrose Synthase and the SWEET Transporter, Which Are Associated With Sugar Hydrolysis and Transport, Respectively, Increases the Hexose Content in Vitis vinifera L. Grape Berries - Ren, Ruihua; Yue, Xiaofeng; Li, Junnan; Xie, Sha; Guo, Shuihuan; Zhang, Zhenwen (Frontiers in Plant Science, 2020)
The sugar content of grape berries is affected by many factors. To explore the hexose-content in different cultivars, the photosynthesis, vegetative and reproductive biomass, enzyme activities and expression levels of genes related to sugar metabolism and sugar contents were measured. Samples were collected 70-110 day after anthesis (DAA), from Riesling (RI), Petit Manseng (PM) and Cabernet Sauvignon (CS) berries cultivated in the field. The results indicated that high expression levels of VvSWEET15 and VvSS3 and high activity of sucrose synthase (SS) are associated with the higher hexose content in the berries of PM than in the berries of the other two cultivars. These genes promoted hexose accumulation in the berries by regulating sugar hydrolysis and transport. The results of this study indicate that active sugar hydrolysis and transport increase the hexose content in PM berries, which provides insight for improvement and breeding projects for grape berry quality for wine production.